(untitled) (ModaPalavra e-periódico, 2016)
The article discusses the memory of the costumes and the way people record and interpret their relations with them. This is on the assumption that we put ourselves at all, and for that reason, too, the popular costumes reveal the political place of eachsubject on the Festa de São Benedito in Congada de Ilhabela -manifestation of African descent culture chosen to treated in this text. This study aimed to understand the role of costume in the composition of the cultural identity of black ethnic-racial group of Ilhabela, to point out how a seemingly simple costume can reveal so many meanings for the group in question. The Congada de Ilhabela is the devotion of a population to a saint; holy and black people who resisted the many prejudices and deep social and economic transformations. Therefore, the expression of that culture and tradition invented by means of a negotiated identity will be discussed. Regarding the costume, the study will be based on material culture and participant observation conducted withthis population between the years 1995 to 2002.